2012
DOI: 10.1021/jo201800u
|View full text |Cite
|
Sign up to set email alerts
|

2-Acylamino-6-pyridones: Breaking of an Intramolecular Hydrogen Bond by Self-association and Complexation with Double and Triple Hydrogen Bonding Counterparts. Uncommon Steric Effect on Intermolecular Interactions

Abstract: 2-Acylamino-6-pyridones (acyl = RCO, where R = Me, Et, i-Pr, t-Bu, and 1-adamantyl) were previously characterized by X-ray diffractometry and solid-state NMR techniques by us. One of these compounds was used recently in organocatalysis. The series is now studied in solution and by computational methods recommended for noncovalent interactions (DFT/M05). These compounds showed interesting behavior during dilution and titration experiments monitored by (1)H NMR. 2-Acylamino-6-pyridones change their conformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 69 publications
2
31
0
Order By: Relevance
“…Moreover, the same approach has been used to study the hydrogen bond bridges in which the hydrogen bond acceptor carries three (FHÁÁÁFF [58], NHÁÁÁF, CHÁÁÁF [59]), two (NHÁÁÁO, or OHÁÁÁO [54]), and one lone electron pair (FHÁÁÁNH 3 [59]). This method have also been used in explaining the properties of intramolecular hydrogen bonds (NHÁÁÁN [60]) and intermolecular ones that stabilize dimer, trimers and tune the properties of rotamers in supramolecular assemblies [16,61]. It is fair to mention that we used this approach to highlight the differences in energy of interactions between NHÁÁÁN/O and CHÁÁÁN/O contacts, while the QTAIM was shown to be applicable for many structures where the hydrogen bonding is described as purely non-covalent interaction (even a weak one [62]) or it is considered as partially covalent one with relatively high bond orders [63].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the same approach has been used to study the hydrogen bond bridges in which the hydrogen bond acceptor carries three (FHÁÁÁFF [58], NHÁÁÁF, CHÁÁÁF [59]), two (NHÁÁÁO, or OHÁÁÁO [54]), and one lone electron pair (FHÁÁÁNH 3 [59]). This method have also been used in explaining the properties of intramolecular hydrogen bonds (NHÁÁÁN [60]) and intermolecular ones that stabilize dimer, trimers and tune the properties of rotamers in supramolecular assemblies [16,61]. It is fair to mention that we used this approach to highlight the differences in energy of interactions between NHÁÁÁN/O and CHÁÁÁN/O contacts, while the QTAIM was shown to be applicable for many structures where the hydrogen bonding is described as purely non-covalent interaction (even a weak one [62]) or it is considered as partially covalent one with relatively high bond orders [63].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, as shown in Figure (d), the strong repulsion between the positive H methyl (+0.208) and the positive hetero‐S atom (+0.439) is contradictory to the syn preference of 2‐[5]1S + 30 b . In fact, besides of the electrostatic factor, it has been found that the repulsion and steric effects within molecules act in similar way but cause quite opposite effects. So, the steric and quantum factors also need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The M05 functional suggested for non-covalent interactions [40, 41] was used together with the 6-311+G(2d,2p) basis set as in previous publications [18, 21, 22]. The use of the diffuse functions is crucial for describing the anionic specie, while polarization functions are used to properly describe the hydrogen bonding.…”
Section: Methodsmentioning
confidence: 99%
“…The use of the diffuse functions is crucial for describing the anionic specie, while polarization functions are used to properly describe the hydrogen bonding. Optimizations were performed with the use of PCM model of solvation [42] in chloroform since in previous publications such treatment was in agreement with experimental results [18, 21, 22]. For all optimized structures the frequency calculations were ran to check if the geometry is in energy minima (only positive frequencies were obtained).…”
Section: Methodsmentioning
confidence: 99%